On the endowment effect in `apple-mars’ experiments - Haagsma, R.; Mouche, P. v. (Applied Studies in Agribusiness and Commerce, 2016)
In this article we take a close look at a specific type of behavioural experiment that Antonides conducted to study the endowment effect. We argue that if such experiments ignore to test for the presence of persons in the sample who are indifferent between alternatives, the identification procedure for establishing an endowment effect is fallible.